Hierarchical and ultrathin copper nanosheets synthesized via galvanic replacement for selective electrocatalytic carbon dioxide conversion to carbon monoxide - Pan, Jing (2021)
Electrochemical conversion of carbon dioxide (CO2) to desirable products with high selectivity and efficiency remains critical challenges in balancing carbon cycle for sustainable society. Herein, we demonstrate the hierarchical porous architectures assembled by ultrathin copper (Cu) nanosheets (NS) via a simple galvanic replacement method for the improved selectivity of CO2 conversion with a large current density. Specifically, the optimized hierarchical Cu electrodes achieve high selectivity and activity to convert CO2 into CO, showing a Faradaic efficiency (FE) of 74.1%, record-high partial current density of 23.0 mA cm−2, and turnover frequency of 0.092 s-1 for CO product as well as FE of 24.8% for H2 at potential of -1.0 V vs RHE. The onset potential for the CO2 conversion is -0.29 V vs RHE. Theoretical calculations indicate that the abundant vacancy defects exposed on ultrathin Cu nanosheets can accelerate the initial kinetics of CO formation during the CO2 conversion process. As demonstrated by experimental and computational analyses, the unique hierarchical architecture of integrated Cu electrode contributes the outstanding electrocatalytic performance due to the rapid mass and electrons transport as well as the abundant active sites and associated intrinsic activity.